IoT-Enabled Smart Operating Rooms for Enhancing Surgical Efficiency - Tushar Jadhav; Monali Gulhane; Saurabh Bhattacharya; Vinit Khetani; Yatin Gandhi; Dhananjay R Dolas (Journal of Neonatal Surgery, 2024)
The internet of things (IoT) is revolutionizing the healthcare enterprise, mainly in the enhancement of surgical environments through the development of IoT-enabled clever working rooms. these progressive systems combine a network of sensors, devices, and software solutions to optimize surgical workflows, enhance patient effects, and minimize human errors. The core of this change lies in the capability to gather and examine actual-time records, facilitating on the spot and knowledgeable choice-making for the duration of surgical methods. This paper explores the deployment of IoT technologies in running rooms and their impact on surgical efficiency and safety. We talk the integration of diverse IoT gadgets, such as computerized surgical tools, environmental sensors, and wearable devices for each patients and surgical body of workers. those factors work collectively to create a cohesive environment that complements the operational factors of surgery, which include instrument readiness, sterilization methods, and the monitoring of patient vitals and surgical progress. furthermore, we deal with the demanding situations and answers related to records security and privateness, that are paramount whilst managing sensitive health facts in actual-time. Implementation strategies that encompass technical, ethical, and regulatory issues are evaluated to make certain that these advanced systems can be appropriately and effectively integrated into cutting-edge healthcare practices. The capability of IoT-enabled clever running rooms to transform surgical practices is substantial. more desirable statistics-pushed insights and the automation of routine tasks free up scientific professionals to focus more on crucial surgical decisions and patient care, hence elevating the general performance and effectiveness of surgical interventions.